Augmenting inter‐rater concordance of radiologic extranodal extension in HPV‐positive oropharyngeal carcinoma: A multicenter study. Issue 11 (29th June 2022) - Hoebers, Frank; Yu, Eugene; O'Sullivan, Brian; Postma, Alida A.; Palm, Walter M.; Bartlett, Eric; Lee, Jonathan; Stock, Sarah; Koyfman, Shlomo; Su, Jie; Xu, Wei; Huang, Shao Hui
Abstract: Objectives: To assess intra‐ and inter‐institutional concordance and identify methods to increase precision in radiologic extranodal extension (rENE) ascertainment in HPV+ oropharyngeal carcinoma. Methods: Six radiologists, blinded to clinical outcomes, from three centers assessed rENE in two phases: Phase‐I (20 cases) utilized each individual's a priori appreciation of the literature. Phase‐II (30 additional cases) was performed after deliberating experience and consolidating operating definitions. Intra‐ and inter‐institutional Kappa were calculated at >50% and >75% certainty levels, respectively. Results: The Phase‐I intra‐institutional kappa was 0.76, 0.32, and 0.44 at >50% certainty and improved to 0.89, 0.61, and 0.66 at >75% certainty. Inter‐institutional Fleiss' kappa also improved with higher certainty (from 0.40 to 0.57, p = 0.039).  The Phase‐II inter‐rater kappa was significantly higher than Phase‐I at the same certainty level (both p  < 0.001). Conclusion: A learning curve exists for rENE assessment. Strategies to augment reliability include high certainty for declaration, consolidated operating definitions, and sharing experience among radiologists.